Prostate cancer risk among French farmers in the AGRICAN cohort - Clémentine Lemarchand; Séverine Tual; Mathilde Boulanger; Noémie Levêque-Morlais; Stéphanie Perrier; Bénédicte Clin; Anne-Valérie Guizard; Michel Velten; Emma Rigaud; Isabelle Baldi; Pierre Lebailly (Nordic Association of Occupational Safety and Health (NOROSH), 2016)
OBJECTIVES: Prostate cancer is one of the most frequent cancers among men worldwide. Its etiology is largely unknown, but an increased risk has been repeatedly observed among farmers. Our aim was to identify occupational risk factors for prostate cancer among farmers in the prospective cohort study AGRICAN. METHODS: Data on lifetime agricultural exposures (type of crops, livestock and tasks including pesticide use, re-entry and harvesting) were collected from the enrolment questionnaire. During the period from enrolment (2005-2007) to 31 December 2009, 1672 incident prostate cancers were identified. Hazard ratios (HR) were estimated using Cox regression analysis. RESULTS: We found an increased risk for cattle breeders using insecticides [HR 1.20, 95% confidence interval (95% CI) 1.01-1.42] with a significant dose-response relationship with number of cattle treated (P for trend 0.01). A dose-response relationship was also observed with the number of hogs (P for trend 0.06). We found an excess of prostate cancer risk among people involved in grassland activities, mainly in haymaking (HR 1.18, 95% CI 1.02-1.36). Pesticide use and harvesting among fruit growers were associated with an elevated prostate cancer risk, with a two-fold increased risk for the largest area. For potato and tobacco producers, an elevated prostate cancer risk was observed for almost all tasks, suggesting a link with pesticide exposure since all of them potentially involved pesticide exposure. CONCLUSIONS: Our analysis suggests that the risk of prostate cancer is increased in several farming activities (cattle and hog breeding, grassland and fruit-growing) and for some tasks including pesticide use.